Migration Diversity and Social Cohesion Reassessing the Dutch Policy Agenda - Jennissen, Roel (Research for Policy, 2023)
This open access book shows policymakers which initiatives work when responding to the increasing diversity in cities, towns and neighborhood's. In recent times, policymakers have grappled with ways of responding to this increase, which has resulted in a plethora of policy initiatives, some more effective than others. Bringing together a large amount of research and evidence-based policy recommendations, this book offers both a sense of strategic direction as well as more specific, actionable advice. It brings together a remarkable mixture of policy areas that touch upon issues of diversity, immigration policy, education, and labour policy. It is of benefit and importance to all those making policies for a country with increasing immigration.